Głos w sprawie publiczności teatralnej. "Siostrzana dusza. Z pamiętników dramaturga" Władysława Sabowskiego = About the theatre audience. "Soulmate. Of the playwrighter's memories" ["Siostrzana dusza. Z pamiętników dramaturga"] by Władysław Sabowski - Narolska, Aneta (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
Published in the fourth issue of "The Music and Theatre Echoes" ["Echa Muzyczne i Teatralne"] (1886) text entitled "Soulmate. Of the playwrighter's memories" by Władysław Sabowski concerns artistic themes. The text refers to the polemics held in the magazine about the role and tasks of the theatre audience i.a. articles "Our audience" by Stanisław Koźmian or "Yet about ?Our audience?" by Edward Lubowski. The work's message speaks of the non-existence of ideal recipients of art, deciphering the senses and symbolic meanings hidden in the work. To formulate them the author evokes Aleksander Fredro's comedy "Recluses and a poet" ["Odludki i poeta"] and the story by Tomasz Teodor Jeż "Soulmates" ["Siostrzane dusze"].
Keywords: Sabowski, Władysław (1837-1888); "Siostrzana dusza"; publiczność teatralna; "Soulmates"; theatre audience